Saturation transfer difference nuclear magnetic resonance titrations reveal complex multistep-binding of l-fucose to norovirus particles - Mallagaray, Alvaro; Hansman, Grant S. (Glycobiology, 2017)
Recently, combined nuclear magnetic resonance (NMR), native mass spectrometry (MS) and X-ray crystallographic studies have demonstrated that binding of histo-blood group antigens (HBGAs) to norovirus capsid protein (P-dimers) is a cooperative process involving four binding pockets. Here, we show that binding to norovirus virus-like particles (VLPs) is even more complex. We performed saturation transfer difference (STD) NMR titration experiments with two representative genotypes of norovirus VLPs using l-fucose as a minimal HBGA. Compared to titrations with P-dimers, the corresponding binding isotherms reflect at least six distinct binding events.
Gesehen am 05.09.2018
Advance access publication date: 27 August 2016